2015
DOI: 10.1186/s13041-015-0101-6
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-lipoic acid treatment is neurorestorative and promotes functional recovery after stroke in rats

Abstract: The antioxidant properties of alpha-lipoic acid (aLA) correlate with its ability to promote neuroproliferation. However, there have been no comprehensive studies examining the neurorestorative effects of aLA administration after the onset of ischemia. The middle cerebral artery (MCA) of adult rats was occluded for 2 hours and then reperfused. aLA (20 mg/kg) was administered in 71 animals (aLA group) through the left external jugular vein immediately after reperfusion. An equivalent volume of vehicle was admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 62 publications
0
32
0
3
Order By: Relevance
“…1D). Compared with the Control group, the LA20 group (10 [8, 12]) and LA40 group (13 [10, 15]) had significantly improved neurological outcomes (both P < 0.05). There was a statistical difference between the LA20 and LA40 groups, with the Garcia score in the LA40 group significantly improved ( P < 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1D). Compared with the Control group, the LA20 group (10 [8, 12]) and LA40 group (13 [10, 15]) had significantly improved neurological outcomes (both P < 0.05). There was a statistical difference between the LA20 and LA40 groups, with the Garcia score in the LA40 group significantly improved ( P < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…These properties make LA a perfect antioxidant for the treatment of brain disease. The neuroprotective effect of LA has been demonstrated in different animal models of cerebral ischemia reperfusion injury [12, 30, 31]. Clark et al [30] demonstrated that LA pretreatment (100 mg/kg, subcutaneously) significantly reduced stroke infarct volume and promoted neurological function at 24 h post reperfusion in a focal cerebral reperfusion model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For all these reasons, aL" is a great candidate to start clinical trials as neurorestorative of brain tissue [111].…”
Section: Immune Response As a Neurorestorative Mechanismmentioning
confidence: 99%